Diagnostic usefulness of FibroMeter VCTE for hepatic fibrosis in patients with nonalcoholic fatty liver disease - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2015)
BackgroundLiver fibrosis is an important prognostic determinant in patients with nonalcoholic fatty liver disease (NAFLD). The FibroMeter VCTE is a diagnostic tool comprising both biochemical markers and transient elastography (TE) originally developed for the diagnosis of fibrosis in patients with chronic viral hepatitis. In this pilot study, we investigated the diagnostic performance of the FibroMeter VCTE tool for determining fibrosis in patients with biopsy-proven NAFLD. Its diagnostic accuracy was also compared with those of the NAFLD fibrosis score (NFSA) and TE alone.Patients and methodsFibroMeter VCTE, NFSA, and TE were determined in 52 patients with NAFLD. The results of liver biopsies were considered the gold standard. Areas under the receiver operating characteristic curve were used to express the diagnostic accuracy of each test.ResultsSignificant (F2) and severe (F3) fibrosis were detected in 20 (38%) and 10 (19%) patients, respectively. The sensitivity of FibroMeter VCTE, NFSA, and TE for detecting significant fibrosis was 70, 65, and 75%, respectively, whereas specificity was 88, 81, and 78%. The sensitivity of FibroMeter VCTE, NFSA, and TE for diagnosing severe fibrosis was 90, 90, and 100%, respectively, whereas specificity was 93, 78, and 76%. Receiver operating characteristic analysis showed that FibroMeter VCTE had a significantly larger areas under the receiver operating characteristic curve (0.968) compared with both NFSA (0.833, P<0.001) and TE (0.922, P<0.05) for the detection of severe fibrosis.ConclusionOur preliminary findings indicate that FibroMeter VCTE is superior to both NFSA and TE for the diagnosis of severe fibrosis in patients with NAFLD.
Keywords: accuracy; diagnostic scores; fibrosis; nonalcoholic fatty liver disease; transient elastography; SIMPLE NONINVASIVE INDEX; TRANSIENT ELASTOGRAPHY; CLINICAL-APPLICATION; SCORING SYSTEM; NAFLD; PREDICT; VALIDATION; MORTALITY